A systematic review of randomised controlled trials using Acceptance and commitment therapy as an intervention in the management of non-malignant, chronic pain in adults. (June 2017) - Simpson, Peter A.; Mars, Tom; Esteves, Jorge E.
Abstract: Context: Acceptance and Commitment Therapy (ACT) is a psychological, behavioural based intervention used in the management of chronic pain (CP). CP represents a significant challenge for health care professionals including osteopaths. Whilst support for ACT's effectiveness is present in peer reviewed literature, the validity and generalisability of reported findings is negatively affected by methodological flaws and trial heterogeneity. A systematic review of randomised controlled trials (RCTs) of ACT as an intervention in the management of non-malignant, CP in adults was conducted to evaluate the effectiveness of ACT. Method: Systematic online searches for RCTs and evaluation using methodological quality criteria. Literature search: 110 trials were identified of which 93 were duplicates, 17 were assessed for eligibility, 4 were excluded according to criteria and 3 for high risk of bias. 10 trials were reviewed. Results: Evidence exists in support of the effectiveness of ACT in managing CP. Evidence regarding process mediators of behavioural change in ACT is insufficient and conflicting. Meta-analysis was precluded due to heterogeneity in the sample. Conclusions: ACT demonstrates promise as a therapeutic intervention for non-malignant, CP populations. Evidence regarding mediation of behavioural change is conflicting. Heterogeneity in the sample precludes meta-analysis. Generalisability was supported by corroborating evidence across numbers of trials. Further research is indicated to develop the utilisation of ACT in conjunction with manual therapies as an intervention for CP.